A dilemma in management of intrauterine death in mother with major placenta previa - Rima Anggrena Dasrilsyah; Yulianty Arifuddin; Nor Azlin Mohamed Ismail (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Placenta previa is a condition when the placental tissue extends over the internal cervical os. It is associated with maternal and fetal morbidity and mortality. With intrauterine death, the mode of delivery will be more difficult to decide. Here, we report a case of 30 years old G3P2 with placenta previa major diagnosed with intrauterine death at 29 weeks gestation who was managed conservatively and delivered vaginally with minimal complication. A good patient selection and thorough counseling, patient with placenta previa major and intrauterine death still can be safely delivered vaginally.